Acquired infection during neonatal and pediatric extracorporeal membrane oxygenation. (September 2018) - Cashen, Katherine; Reeder, Ron; Dalton, Heidi J.; Berg, Robert A.; Shanley, Thomas P.; Newth, Christopher J. L.; Pollack, Murray M.; Wessel, David; Carcillo, Joseph; Harrison, Rick; Dean, J. Michael; Tamburro, Robert; et al.
Introduction: Our objectives are to (1) describe the pathogens, site, timing and risk factors for acquired infection during neonatal and pediatric ECMO and (2) explore the association between acquired infection and mortality. Methods: Secondary analysis of prospective data collected by the Collaborative Pediatric Critical Care Research Network between December 2012 and September 2014. Clinical factors associated with acquired infection were assessed with multivariable Cox regression. Factors associated with mortality were assessed with logistic regression. Results: Of 481 patients, 247 (51.3%) were neonates and 400 (83.2%) received venoarterial ECMO. Eighty (16.6%) patients acquired one or more infections during ECMO; 60 (12.5%) patients had bacterial, 21 (4.4%) had fungal and 11 (2.3%) had viral infections. The site of infection included respiratory for 53 (11.0%) patients, bloodstream for 21 (4.4%), urine for 20 (4.2%) and other for 7 (1.5%). Candida species were most common. Median time to infection was 5.2 days (IQR 2.3, 9.6). On multivariable analysis, a greater number of procedures for ECMO cannula placement was independently associated with increased risk of acquired infection during ECMO (Hazard Ratio 2.13 (95% CI 1.22, 3.72), p<0.01) and receiving ECMO in a neonatal ICU compared to a pediatric or cardiac ICU was associated with decreased risk (Hazard Ratio pediatric ICU 4.25 (95% CI 2.20, 8.20), cardiac ICU 2.91 (95% CI 1.48, 5.71), neonatal ICU as reference, p<0.001). Acquired infection was not independently associated with mortality. Conclusion: ECMO procedures and location may contribute to acquired infection risk; however, acquired infection did not predict mortality in this study.